2004
DOI: 10.1016/s0002-9440(10)63233-6
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the Nf1 Tumor Suppressor Gene Decreases Fas Antigen Expression in Myeloid Cells

Abstract: Genetic loss of surface Fas antigen expression leads to reduced apoptosis of myeloid and lymphoid progenitor cells, and a propensity to develop autoimmunity and myeloid leukemia in mouse models. Oncogenic p21 ras decreases surface Fas antigen expression and renders fibroblasts resistant to Fas mediated apoptosis. Neurofibromin, which is encoded by NF1, is a GTPase activating protein that negatively regulates p21 ras activity. NF1 loss leads to deregulation of p21 ras -effector pathways, which control myeloid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…[16][17][18] This notion is supported by the observations that various Nf1-deficient cells survive in the absence of trophic factors 19 and that enhanced survival of Nf1-deficient sensory neurons is dependent on Ras. [19][20][21] It is nevertheless possible that the proapoptotic action of neurofibromin is also exerted independently of Ras. The aim of the present study was to verify the existence of a proapoptotic action of neurofibromin, and -if confirmed -to determine the extent to which this putative action is dependent on Ras.…”
mentioning
confidence: 99%
“…[16][17][18] This notion is supported by the observations that various Nf1-deficient cells survive in the absence of trophic factors 19 and that enhanced survival of Nf1-deficient sensory neurons is dependent on Ras. [19][20][21] It is nevertheless possible that the proapoptotic action of neurofibromin is also exerted independently of Ras. The aim of the present study was to verify the existence of a proapoptotic action of neurofibromin, and -if confirmed -to determine the extent to which this putative action is dependent on Ras.…”
mentioning
confidence: 99%
“…54 Loss of the NF1 GAP in hematopoietic cells, including but not limited to mast cells, increases the latency and potency of GTP-bound Ras and phosphorylated downstream effectors within the Raf-mitogen-activated protein (MAP)/extracellular signalrelated kinase (ERK) kinase (MEK)-ERK and phosphoinositide-3-kinase (PI3K)-Rac-p21-activated kinase (Pak)-P38 pathways. 36,57,59,[64][65][66][67][68][69][70] SCF-dependent c-kit signaling in the mast cell hinges specifically on K-ras pathways. 67 Immunoprecipitation experiments indicate that SCF:c-kit-activated Ras induces a cascade ultimately phosphorylating and activating p44/p42 (ERK1/2), p38, and AKT.…”
Section: Scf-and Nf1-dependent Mast Cell Biochemistrymentioning
confidence: 99%
“…In addition to promoting growth at limiting concentrations of growth factors that may be particularly relevant at physiologic concentrations, Nf1 -/-myeloid progenitors (14) and Nf1 +/-mast cells (13) have increased survival associated with an increase in PI3K activity. To examine whether this phenotype is present in Nf1 +/-osteoclasts, purified osteoclasts were cultured in M-CSF in the absence of serum, and apoptosis was determined sequentially over 24 hours using annexin V staining.…”
Section: Nf1 +/-Mice Have Increased Numbers Of Osteoclast Progenitorsmentioning
confidence: 99%
“…Further, mice transplanted with Nf1 -/-fetal liver hematopoietic stem cells uniformly develop a myeloid leukemia (10,11) that is highly reminiscent of the juvenile myelomonocytic leukemia observed in children with NF1 (12). Recent studies in Nf1 +/-mast cells (7,8,13) and in Nf1 -/-myeloid progenitors (14) link increased activation of the p21 ras /PI3K signaling pathway to multiple neurofibromin-deficient mast cell and myeloid progenitor phenotypes.…”
Section: Introductionmentioning
confidence: 99%